2018
DOI: 10.1177/0265659018780960
|View full text |Cite
|
Sign up to set email alerts
|

Are story retelling and story generation connected to reading skills? Evidence from Finnish

Abstract: This three-year follow-up study investigated the associations of narrative and reading skills in typically developing Finnish children. Twenty children performed narrative retelling and story generation tasks twice, at five and eight years of age. Reading comprehension and word recognition tests were performed at the age of eight. Narratives were analysed for relevant information, total number of word tokens, clausal density and evaluation. The results showed increased narrative abilities with age, but the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…Consequently, different narrative task procedures may yield different results. It is important to emphasize, however, that previous studies have found moderate-to-strong correlations between different aspects of retelling and story generation (Mäkinen et al, 2018;Westerveld & Moran, 2013).…”
Section: Final Remarks and Implications For Future Studiesmentioning
confidence: 88%
See 4 more Smart Citations
“…Consequently, different narrative task procedures may yield different results. It is important to emphasize, however, that previous studies have found moderate-to-strong correlations between different aspects of retelling and story generation (Mäkinen et al, 2018;Westerveld & Moran, 2013).…”
Section: Final Remarks and Implications For Future Studiesmentioning
confidence: 88%
“…The Renfrew Bus Story Test (Renfrew, 1997) is a retelling task in which a child is told a story about a 'naughty bus' while looking at 12 corresponding pictures of how the bus behaved. The scaffolding given using pictures and a model story (Heilmann et al, 2010) might be beneficial for young children's narrative production (see Berman, 1988) and appears to be effective based on the results of previous studies (Bishop & Edmundson, 1987;Mäkinen et al, 2018). Immediately afterwards, the child is asked to retell the story while looking at the pictures.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations